RANCANG BANGUN SISTEM INVENTORY STOK BARANG PADA ANEKA FROZEN FOOD BERBASIS WEB - Lutfi Nugroho (2022)
The current era encourages technology to develop rapidly and have an impact on life. The development and growth that occurs in this technology has an important role in the activities carried out by each individual as well as the company. The presence of this technology can have a positive impact and can foster reliable effectiveness in business processes or activities in a business or company activity. However, based on the interview results, Aneka Frozen Food has not utilized technology optimally. Various Frozen Foods still use the manual method, causing errors such as recording the number of stock items, orders, and sales reports. Based on this, the authors built a web-based system for Aneka Frozen Food to help Aneka Frozen Food accelerate the process of data collection, order recording, and computerized sales reports. The method used in system design is the Waterfall method and PIECES as a system analysis method. The language used in building the system is PHP and the database used is MySQL. With this system, Aneka Frozen Food can collect data on goods, view customer order details and view and print sales reports easily.